1997
DOI: 10.1046/j.1365-2559.1997.d01-626.x
|View full text |Cite
|
Sign up to set email alerts
|

Histology of aberrant crypt foci in the human colon

Abstract: Aberrant crypt foci (ACF) have been identified in the methylene-blue stained mucosa of the human colon. Some lines of evidence suggest that ACF may be precursors of colon cancer. The objective of the present study was to establish morphological criteria able to define and classify ACF in histological sections. Twenty-four colectomy specimens were collected after operation for colorectal cancer and fixed in 10% formalin. Strips of grossly normal mucosa were stained in a 0.2% solution of methylene blue in saline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 13 publications
0
58
0
1
Order By: Relevance
“…ACFs are monoclonal proliferations considered putative precursors of colorectal cancer in both humans and exp er i m e n t a l a n i m a l s b e c a u s e t h e y s h o w m o l e c u l a r abnormalities that occur in and are characteristic of more advanced lesions (32,33). However, several studies have also documented that ACFs are a heterogeneous population of lesions, the majority of ACFs in CRC patients and carcinogentreated rodents being not dysplastic (8,(28)(29)(30)(31)(34)(35)(36)(37). In line with these last observations, we found that only one ACF among those analyzed in CRC patients was dysplastic, whereas the others were hyperplastic or nonhyperplastic/ nondysplastic lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACFs are monoclonal proliferations considered putative precursors of colorectal cancer in both humans and exp er i m e n t a l a n i m a l s b e c a u s e t h e y s h o w m o l e c u l a r abnormalities that occur in and are characteristic of more advanced lesions (32,33). However, several studies have also documented that ACFs are a heterogeneous population of lesions, the majority of ACFs in CRC patients and carcinogentreated rodents being not dysplastic (8,(28)(29)(30)(31)(34)(35)(36)(37). In line with these last observations, we found that only one ACF among those analyzed in CRC patients was dysplastic, whereas the others were hyperplastic or nonhyperplastic/ nondysplastic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Lesions showing dysplastic features were classified as microadenomas (25,26) with low or moderate grade of dysplasia (27, 28). Lesions showing no dysplasia were classified as hyperplastic lesions (25,26) or nondysplastic/nonhyperplastic lesions according to previously described criteria (28)(29)(30).…”
Section: Histology Of the Observed Lesionsmentioning
confidence: 99%
“…For in-depth review of the experimental and human observational evidence on the phenotypes and genetic and epigenetic spectra of ACF, see Pretlow and Pretlow [9] and Alrawi et al [10]. For detailed description of histopathological features of ACF see Hurlstone and Cross [11] and Di Gregorio et al [12].…”
Section: Rationale For This Reviewmentioning
confidence: 99%
“…ACF were classified in to three groups according to cytological and histological criteria (Di Gregorio et al, 1997). ACF in the first group (group A) had only mild alterations (referred to as 'hypertrophy'), namely enlarged crypts (at least 1.5 times larger than normal) with only slightly enlarged and elongated nuclei, but no crowding or stratification, and no mucin depletion or dysplasia.…”
Section: Histologymentioning
confidence: 99%